Workflow of Ukrainian National Antarctic Scientific Centre portal modeling - Globa, L.S.; Novogryska, R. L. (Ukrainian Antarctic Journal, 2015)
The methodology of workflows automatization in complex information distributed systems is described. Such methodology allows to improve the efficiency of scientists interaction bу automated workflows of data processing description аnd modeling. Such workflows of data processing form the basis of the National Antarctic Scientific Сеntеr activities in the context of the "National Antarctic Data Centre" the development. The model of workflows "NASC data processing" automatization is suggested. As the result the workflow model is received that allows to describe general workflow in the complex informational-communicational distributed environment of National Antarctic Scientific Center of Ukraine.